The Personality of A Muslim Educator in The Perspective of Islamic Philosophy of Education - Nurman Hasibuan; Salminawati Salminawati; Usiono Usiono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The personality of a Muslim educator is a matter of great urgency in Islamic education. Muslim personality is defined as the identity possessed by an individual as a distinctive feature of their overall behavior as a good Muslim. This study will discuss the personality of a Muslim educator with a formulation of the understanding of the personality of a Muslim educator in the perspective of Islamic philosophy of education, the elements of Muslim personality formation, as well as the duties and responsibilities of educators, and the nature and characteristics of the personality of a Muslim educator. The results of this study include the personality of a Muslim educator as a unity that exists within the soul of an educator, which is truly obtained by everyone who emulates the characteristics of Allah SWT and the personality of the Prophet Muhammad. The elements of human personality formation consist of the body, soul, heart, intellect, traits, and characteristics of Muslim educators, including not only intelligence and perfect reasoning but also good manners and physical strength.